Hands-on Experience with Altera FPGA Development Boards - Parab, Jivan S. (Springer India, 2018)
This book is built around the use of readymade soft processor cores for FPGA design. In particular, the book focuses on Altera FPGA boards. The book explores many different embedded systems needs and prepares its readers for hands-on design and development of such systems. Many worked-out examples and case studies have been included to enable a clear understanding of design concepts. Primarily designed as a textbook for core or lab courses on FPGA based embedded systems, this book will appeal to students and instructors alike. The book takes an autodidactic approach, which also makes it suitable for hobbyists and practitioners looking to acquaint themselves with Altera FPGA boards.